Teknologi dan Tugas Panggilan Gereja : (Sebuah Analisis Teoritis - Pemanfaatan Teknologi dalam Merealisasikan Tugas Panggilan Gereja - Silitonga, Pranitha (JURNAL DIAKONIA, 2022)
Tecnology is a knowledge process that affects all aspects of human life both in terms of education, economy and politics. One of the communities that cannot be seperated from technological developments is the church. Seeing the development of church tecnology, it is recommended to be inclusive to accept the times, especially tecnology which is always changing. This is due to the fact that without realizing it, technology affects the entire existence of human life, strating from children, teenagers, parents, communities and even certain organizaations. The church must be able to follow the ministry in accordance with the context that exists in the offline world and need to do it also in the online world, so that a balance is achieved and the church’s duties remain relevant in its functioning in the current tecnological era called 4.0.